The fragmentation of public administration: Differentiated and decentered governance in the (dis)United Kingdom. (26th November 2021) - Elliott, Ian C.; Bottom, Karin A.; Carmichael, Paul; Liddle, Joyce; Martin, Steve; Pyper, Robert
Abstract: This paper analyzes a UK polity that is characterized by fragmentation, differentiation, and decentered governance which is evident at multiple layers of public policy and administration. The development of devolved governments as well as ongoing debates around regional and local governance have created increasingly fragmented places. The intensification of policies associated with the new public management has fragmented the provision of public services. And the absence of a common approach to professional development has led to growing fragmentation of public service workers from different professions and sectors. We argue that these trends reflect many of the aspects of an advanced or late‐stage new public governance. This is ripe territory for further research and demonstrates that UK public administration continues to have much to offer to international scholars. It also raises important questions about what forms of public administration might emerge next.